Durable complete response to PD-1 inhibitor in vesical calculus-associated squamous cell carcinoma: a case report - Dong, Xingwang; Fu, Xiaobao; Zhang, Hanghao; Ma, Yingjun; Wang, Cheng; Li, Ye; Zhang, Su (Frontiers in Immunology, 2025)
BackgroundBladder squamous cell carcinoma (SCC) is a rare histological subtype of bladder cancer (1%–5% of cases), with radical cystectomy as the primary recommended treatment. However, evidence for neoadjuvant/adjuvant chemotherapy or immunotherapy remains limited, especially for calculus-associated SCC.Case presentationA 45-year-old male with vesical calculus-associated bladder SCC refused surgery and radiotherapy, and discontinued gemcitabine-cisplatin chemotherapy due to severe toxicity. He received tislelizumab (programmed death-1/PD-1 inhibitor, 200 mg q3w) and achieved a complete response (CR) after 8 cycles. Suprapubic cystolithotomy was safely performed during immunotherapy, and no tumor recurrence was observed for >24 months. Throughout the entire immunotherapy course, no severe immune-related adverse events occurred.ConclusionTislelizumab monotherapy may be a viable option for surgery-ineligible or chemotherapy-intolerant calculus-associated bladder SCC. Definitive stone removal under immunological tumor control is feasible, supporting further exploration of PD-1 inhibitors in this rare subtype.